Perancangan Perbaikan Pada Mesin Slicer Untuk Meminimasi Jumlah Defect Pada Proses Slicing di Perusahaan Meat Processing Menggunakan Metode QFD - Muhammad Thoriq Faza; Wiyono Sutari; Sheila Amalia (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Product quality is conformity to requirements or specifications, which is greatly influenced by the production process. PT XYZ is a company in the meat processing sector, producing products such as smoked beef. There are 11 CTQs that must be met in smoked beef production, but there is still a gap between the number of defects and the maximum permitted limit. The slicing process is the main cause of the highest number of defects. This research aims to identify factors that cause defects in the slicing process and design a proposed machine to reduce the number of defects. The DMAI method is used to find solutions, followed by QFD to fulfill consumer desires. The design includes the addition of a proximity sensor, increased knife speed, and an integrated knife sharpener. A proximity sensor is connected to a microcontroller to monitor knife rotation speed and thickness in real-time. Providing this tool helps operators monitor machine conditions in real-time and prevent defects. The simulation shows an increase in the sigma level from 4,100 to 4,995.